Active and Passive Destabilization of G-Quadruplex DNA by the Telomere POT1-TPP1 Complex. Issue 7 (2nd April 2021) - Xu, Mengyuan; Axhemi, Armend; Malgowska, Magdalena; Chen, Yinghua; Leonard, Daniel; Srinivasan, Sukanya; Jankowsky, Eckhard; Taylor, Derek J.
Graphical abstract: Highlights: The telomere POT1-TPP1 complex binds and destabilizes G-quadruplex (G4) structures. POT1-TPP1 destabilizes G4 via both passive capture and active destabilization. Cancer-related mutations in POT1 differentially affect G4 binding and destabilization. Abstract: Chromosome ends are protected by guanosine-rich telomere DNA that forms stable G-quadruplex (G4) structures. The heterodimeric POT1-TPP1 complex interacts specifically with telomere DNA to shield it from illicit DNA damage repair and to resolve secondary structure that impedes telomere extension. The mechanism by which POT1-TPP1 accomplishes these tasks is poorly understood. Here, we establish the kinetic framework for POT1-TPP1 binding and unfolding of telomere G4 DNA. Our data identify two modes of POT1-TPP1 destabilization of G4 DNA that are governed by protein concentration. At low concentrations, POT1-TPP1 passively captures transiently unfolded G4s. At higher concentrations, POT1-TPP1 proteins bind to G4s to actively destabilize the DNA structures. Cancer-associated POT1-TPP1 mutations impair multiple reaction steps in this process, resulting in less efficient destabilization of G4 structures. The mechanistic insight highlights the importance of cell cycle dependent expression and localization of the POT1-TPP1 complex and distinguishes diverse functions of this complex in telomere maintenance.